Extrapleural Closure of Patent Ductus Arteriosus: How We Do It - Pradegan,Nicola (2020)
Abstract Patent ductus arteriosus (PDA) is a clinical condition mostly found in premature newborns. Among several medical, surgical and interventional treatment options, extrapleural ligation through a left minithoracotomy is recognized as a safe, efficient and less expensive technique. In fact, it requires short surgical times, grants good exposure of the duct and nearby structures (e.g., thoracic duct, left recurrent laryngeal nerve), and avoids pleural space opening and subsequent pulmonary complications in preterm patients. This approach seems ideal due to its lower costs, especially in developing countries with a high birth rate and limited resources.